Titus Groan’s Journey: From Gormenghast to the City - Jakovljević, Mladen M. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The protagonist’s passage from the world of Gormenghast in Mervyn Peake’s Titus Groan and Gormenghast, the first two volumes of the story, to the futuristic world of the City in the third volume, Titus Alone, is often seen as a break between the two worlds. This unexpected passage from one world to another also brings an unexpected switch to science fiction. Both these changes, the passage to another, radically different world and a shift to science fiction, are not so abrupt or radical as they may seem on the surface. Placing the Gothic and science fiction features into the spotlight, while not denying the existence and importance of others, can show how the reality in the trilogy is shaped, how its two worlds are connected into a whole, and how to give one another shape in the overall picture of Gormenghast. Together, they can add to the illumination of the anomaly of Mervyn Peake’s story of Gormenghast.